2011
DOI: 10.1016/j.cej.2010.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Removal of aqueous toxic Hg(II) by synthesized TiO2 nanoparticles and TiO2/montmorillonite

Abstract: Abstract:The adsorption and photocatalytic reduction of toxic Hg(II) in aqueous solutions at different temperatures were investigated with synthesized TiO 2 nanoparticles and TiO 2 /montmorillonite. The latter were tested by TGA, BET, TEM and XRD methods. The 9.1nm diameter TiO 2 nanoparticles had a specific surface area exceeding 200 m 2 g -1 . High purity anatase TiO 2 nanoparticles were produced at 500 C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(24 citation statements)
references
References 69 publications
2
21
0
1
Order By: Relevance
“…Так у ряді робіт вказують на достатньо високі сорбційні властивості пілардованих глин щодо вида-лення арсенатів з водного середовища [7][8][9], ртуті [10].…”
Section: літературний оглядunclassified
“…Так у ряді робіт вказують на достатньо високі сорбційні властивості пілардованих глин щодо вида-лення арсенатів з водного середовища [7][8][9], ртуті [10].…”
Section: літературний оглядunclassified
“…Among various metal oxides (Mahdavi et al, 2012), titanium dioxide was proven to have high removal ability toward inorganic and organic pollutants because of its promising properties: high surface area, biological and chemical inertness, high adsorption capacity, photoreactivity, non-toxicity and others (Vassileva et al, 1996;Liang et al, 2000;Engates and Shipley, 2011;Moafi et al, 2011). Different studies were demonstrated that clay mineral/metal oxide composites, prepared by various methods, possess more advantages in removing the organic and inorganic pollutants from wastewaters compared with the pure clay minerals or metal oxides (Ménesi et al, 2008;Doua et al, 2011;Li et al, 2012;Cheng et al, 2013). Several methods such as wet grinding, sol-gel method and pillaring were used for the preparation of clay mineral/TiO 2 composite (Ménesi et al, 2008;Han et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Manganese chloride nanoparticles [23], functionalized iron nanoparticles [13], [24], [25] with particle diameters 100, 40-50 and 10 nm respectively could remove more than 95% Hg(II) at various concentrations. Titania nano particles [14], [26] with diameter ranging from 3-10 nm and large surface area had adsorption capacity of more than 120 mg/g Hg(II) at concentrations ranging from 100-800 mg/L with or without UV illumination. More than 90% of 40-100 ppm Hg(II) in aqueous media was removed by thiol functionalized magnetite nanoparticles [15].…”
Section: Adsorption Kineticsmentioning
confidence: 99%